Me identifico para decidir y construir lo que quiero ser - Ibañez Sánchez, Oliver David (2021)
The purpose of the professional sufficiency work is to develop the construction of identity in the students of the 3rd grade of secondary school with the theme entitled "I identify myself to decide and build what I want to be", in which reflective activities have been taken into consideration and of interaction that are based on the assessment of their personal characteristics, on the vision of each person as unique and unrepeatable, the value of their achievements and potentialities and the overcoming of adversities based on their abilities. In the elaboration of the sessions, the pedagogical and didactic processes of the interpersonal area were taken into consideration to generate an integral development of the skills and values in the students of the 3rd grade of secondary school. Thus, the learning session is based on the problem that generates some difficulties for the construction of personal identity in the adolescent of the 3rd year of secondary school. On the other hand, the strategies that we apply were carefully elaborated to generate full and functional participation in the students with the purpose of effective development.